Determinants of internal audit effectiveness and its mediating role in fraud prevention - Thuy, Lai Thi Thu (Edelweiss Applied Science and Technology, 2025)
This study examines the determinants of internal audit effectiveness and its mediating role in fraud prevention within Vietnamese listed firms. A quantitative approach was adopted, with data collected from 228 internal auditors, chief accountants, CFOs, and audit committee members through structured questionnaires. Using Structural Equation Modeling, the results reveal that auditor competence, independence, information technology adoption, and collaboration between internal and external auditors significantly enhance internal audit effectiveness. In turn, internal audit effectiveness contributes to fraud prevention by strengthening internal controls, promoting transparency, and enabling early risk detection. Managerial support, however, demonstrated neither a direct nor an indirect effect on internal audit effectiveness or fraud prevention. These findings underscore the strategic role of internal audit in corporate governance and emphasize the need for capacity building within audit departments. The study offers practical insights for organizations and policymakers in emerging economies aiming to build robust anti-fraud frameworks and improve internal oversight mechanisms through more effective internal auditing practices.